Comparative Analysis of PF and MLWDF Scheduling Algorithms on LTE Networks for Multimedia Services - Karimah, Siti Amatullah (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2024)
The increase on mobile packet data demand and also the emerging of various kinds of multimedia services is one of the challnging aspect on network cellular development. Convergence multimedia services such as voice over IP and also video demand should be supported by network reliability. To support the increase of multimedia services, 3rd Generation PartnershipProject (3GPP)as standard organization for mobile network technologies have also established 4G network, which is widely used in all over the world today. With the presence of wide range of services in multimedia data, this network must be supported by traffic scheduling to ensure that multimedia service will be deliverd smoothly beetween sender and receiver. This research present performance comparison between two kinds of scheduling algorithm on the 4G network, especially in donwlink traffic which are Proportional Fair (PF) and the Modified Largest Weighted Delay First (MLWDF). This reaserch will show the comparison performance between these two algorith in terms of Quality of Service metric such as delay, packet loss ratio and throughput using LTE-Sim simulator. The simulation result show that MLWDF has best result than PF.